Techno-Economic Analysis in the Production of Copper Nanoparticles by Biosynthetic Method using Citrus medica Linn. Extract - L S Anggiat; R A Fadhilah; F K Insan; G C S Girsang; A B D Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2021)
Copper nanoparticles are the most frequently used materials in the field of nanoscience because of their electrical, optical, biomedical, antifungal, and antibacterial properties. The synthesis of copper nanoparticles with biological methods is known to be environmentally friendly, inexpensive, simple, and capable of producing better nanoparticles than other methods. This study aims to determine the feasibility of an industrial project to manufacture Cu nanoparticles through a biosynthetic method using Citrus medica Linn. extract and evaluate it from an engineering and economic point of view. Some of the parameters used for economic evaluation are Payback Period (PBP), Break Even Point (BEP), and Cumulative Net Present Value (CNPV). The analysis is supported using data taken from online shopping websites. The results showed that the number of Cu nanoparticles that could be produced in one year was 24,000 kg. The total initial capital cost is 272,640.00 USD and the profit is 698,655.90 USD/year. PBP occurred in the 3rd year with the CNPV/TIC value reaching 3.746% in the 9th year. Based on the economic evaluation, the project is concluded to be feasible to run with the anticipated tax and percentage of sales. The results of this study are expected to provide an overview of the economic evaluation of industrial-scale Cu nanoparticles production by biosynthetic method using Citrus medica Linn. extract.